Interactions between hormones and epilepsy. (May 2015) - Taubøll, Erik; Sveberg, Line; Svalheim, Sigrid
Highlights: Complex, bidirectional interdependence between sex steroid hormones and epilepsy. Progesterone and its metabolites are anticonvulsant, estrogens mainly proconvulsant. Androgens are mainly anticonvulsant, but the effects are more varied. Sex steroid hormones affect brain excitability mainly through membrane receptors. Epileptic activity, especially mediated via amygdala, alters reproductive function. Abstract: There is a complex, bidirectional interdependence between sex steroid hormones and epilepsy; hormones affect seizures, while seizures affect hormones thereby disturbing reproductive endocrine function. Both female and male sex steroid hormones influence brain excitability. For the female sex steroid hormones, progesterone and its metabolites are anticonvulsant, while estrogens are mainly proconvulsant. The monthly fluctuations in hormone levels of estrogen and progesterone are the basis for catamenial epilepsy described elsewhere in this issue. Androgens are mainly anticonvulsant, but the effects are more varied, probably because of its metabolism to, among others, estradiol. The mechanisms for the effects of sex steroid hormones on brain excitability are related to both classical, intracellularly mediated effects, and non-classical membrane effects due to binding to membrane receptors. The latter are considered the most important in relation to epilepsy. The different sex steroids can also be further metabolized within the brain to different neurosteroids, which are even more potent with regard to their effect on excitability. Estrogens potentiate glutamate responses, primarily by potentiating NMDA receptor activity, but also by affecting GABA-ergic mechanisms and altering brain morphology by increasing dendritic spine density. Progesterone and its main metabolite 5α-pregnan-3α-ol-20-one (3α-5α-THP) act mainly to enhance postsynaptic GABA-ergic activity, while androgens enhance GABA-activated currents. Seizures and epileptic discharges also affect sex steroid hormones. There are close anatomical connections between the temporolimbic system and the hypothalamus controlling the endocrine system. Several studies have shown that epileptic activity, especially mediated through the amygdala, alters reproductive function, including reduced ovarian cyclicity in females and altered sex steroid hormone levels in both genders. Furthermore, there is an asymmetric activation of the hypothalamus with unilateral amygdala seizures. This may, again, be the basis for the occurrence of different reproductive endocrine disorders described for patients with left-sided or right-sided temporal lobe epilepsy.